Is the clinic the new gym? Non-invasive procedures to increase muscle tone (Canadian Dermatology Today, 2021)
Non-invasive cosmetic procedures have increased 217.3% between 2012 and 2017, allowing for less risk and downtime than traditional aesthetic surgery. Initially with a focus on the face, these procedures have expanded to body contouring, which is defined as modification of the body’s appearance through changes in size or shape. Options for body contouring have expanded beyond liposuction and surgical correction to include many non-invasive energy-based devices, which has resulted in increased patient interest. Statistics from the American Society of Dermatologic Surgery show that the number of treatments for non-invasive body contouring went up by 43% in 2018 in comparison to 2017 and grew four-fold since 2012.